Pembangunan Hukum Dagang Menuju Indonesia Emas - Candra, Andi; Afriani, Kinaria; Ansori, Ansori; Absi, Warmiyana Zairi; Jauhari, Jauhari (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2024)
On the development of the legal system is of course inseparable from the development of other fields, because the development of the legal system is part of the country's development. Legal development must be integrated and coordinated with the development agenda in other fields such as commercial law, which requires a continuous process. Currently, legal developments also need to pay attention to world developments. Here a clear strategy is needed so that legal developments can be harmonized with global developments without abandoning the values of the Indonesian nation. The purpose of this article is to examine the needs for the development of Indonesian commercial law and find a model of trade law reform that we want so that it can meet the needs and support the country's development. The approach taken in this paper is to standardize justice and collect secondary data sources through library research. Qualitative analysis of the collected data. Several provisions of the Criminal Code are outdated, and the related field of law is developing rapidly, which is no longer able to meet the current needs of trade law. Updating Indonesian trade law needs to be carried out immediately to meet developments, the needs of the national community and international demands. There are many modes to choose from for updating Indonesian trade law, including general codification mode, partial codification mode, statutory regulation preparation mode, open codification mode and partial regulation of Indonesian trade law. As trade law develops, it is believed that this will support Indonesia's vision of gold in the future.